Education, Reforms, Enrolment and Drop-out Strategies? - Veresné Valentinyi, Klára (Technical Languages and Translation, 2023)
In this article, we present the results of a representative survey on the grounds of low enrolment and high drop-out at MATE, based on the responses of 31 language teachers and 2161 university students. Two questionnaire surveys were used in the research. The first questionnaire on enrolment consisted of three questions and the second questionnaire on drop-out consisted of seven questions. Based on the responses on enrolment, it can be said that the success of enrolment can be significantly improved by a constant presence at professional promotional events, creative programmes, involvement and information of secondary school students, class teachers and parents, and enthusiastic and creative teachers and programmes.  A significant reduction in drop-outs can be expected through proper university communication towards students, proper timetabling, and avoiding clashes of classes. More attention to student needs, more extra-curricular activities and personal attention are needed. It is important to raise the quality of teaching and to create better IT conditions. Adding credits to language lessons is essential to improve the success of language learning.
Keywords: enrolment; drop-out rate; MATE; questionnaire survey; foreign language learning; Hungarian as a foreign language